THE EVOLUTION OF ORAL REHABILITATION THROUGH IMPLANTONTICS - Cândido de Lima Alves, Diana (Health and Society, 2021)
The scientific article has the theme "The evolution of oral rehabilitation through implantology". The objective of this study is to carry out a literary review on dental implants and to analyze local and systemic factors in the process of osseointegration in oral rehabilitation through dental implants. Our object of study, dental implants, has become an alternative for people who have lost one or more dental elements, and can now count on dental implants that replace the lost dental element. The research problem involves the following questions: Why are there still recurring failures in the osseointegration process? And what does the literature in the area comment and discuss on the topic? This revisionary research is important and justified because, in recent years, we have observed that osseointegration and the installation of implant-supported dental rostheses has become a viable and safe alternative for patients in edentulous situations, specially with regard to rehabilitation procedures. This study hypothesizes that there are still recurrent failures that occur during the period of osseointegration and can be triggered by several local and systemic factors. A bibliographic research was carried out, researching materials already prepared and documentary research of materials not yet analyzed. The initial methodological procedure was to survey scientific articles and books. It was intended to contribute to the knowledge of science and scientific and academic research in the field of dentistry.